Cantor Limit Set of a Topological Transformation Group on S1 - Keying Guan; Zuming Chen (International Journal of Mathematics and Mathematical Sciences)
The limit set of a topological transformation group on S1 generated by two generators is proved to be totally disconnected (or thin) and perfect if the conditions (i–v) are satisfied. A concrete application to a Doubly Periodic Riccati equation is given.